The Correlation between Perfectionism and Fear of Failure among Students in Intensive Arabic Language Program | Al-'Alaqah bayna al-Kamaliyyah wa al-Khawf min al-Fashl li-Tullab al-Barnaamij al-Mukaththaf li-Ta'lim al-Lughah al-'Arabiyyah - M Abdul Hamid; Nur Ila Ifawati; M Abdullah Charis (Al-Ta'rib)
This study aims to describe the classification of perfectionism and fear of failure, as well as the relationship between these two factors in Arabic language learning among students in the intensive program at Maulana Malik Ibrahim University in Malang. This quantitative correlational study utilized a Google Form survey and data analysis using Pearson’s Product Moment Correlation test through SPSS. The results showed that 6.9% of students were in the low perfectionism category, 80.9% were in the moderate category, and 12.1% were in the high category. For fear of failure, 14.3% were in the low category, 72.0% in the moderate category, and 13.7% in the high category. The hypothesis test revealed a significance value of 0.163 (greater than 0.05), indicating no correlation between perfectionism and fear of failure. The Pearson correlation value was -0.057, showing a weak negative relationship between the two. This means that the higher the students' level of perfectionism, the lower their fear of failure, and vice versa.